Novel therapeutic agents for HbF induction: a new era for treatment of β thalassemia? - S.P. Perrine (Thalassemia Reports, 2011)
Fetal globin is endogenous, normally integrated in hematopoietic stem cells in all humans, and available for reactivation. Inducing expression of fetal globin (g-globin) gene expression to 60-70% of a globin synthesis produces β-thalassemia trait globin synthetic ratios, and has been shown to reduce anemia to mild levels which do not require regular blood transfusion. Several classes of therapeutics have induced g-globin expression in β thalassemia patients, raised total hemoglobin levels, and even eliminated transfusion requirements in formerly transfusion-dependent patients, demonstrating proof-of-concept of the approach. However, prior generations of therapeutics were not readily feasible for widespread use. Currently, several recently discovered oral therapeutic candidates are more potent and/ or patientfriendly, requiring low oral doses, have distinct molecular mechanisms of action, and can be used in combination regimens. Tailoring therapeutic regimens to patient subsets stratified for solely β+ or a β0 globin mutation, and for quantitative trait loci (QTL) which modulate HbF and clinical severity, can guide more effective and informative clinical trials. These advancements provide methods for a rational approach to applying fetal globin gene induction in therapeutic regimens suitable for use in diverse thalassemia patient populations world-wide.   胎儿珠蛋白是内生的，通常结合在所有人类的造血干细胞中，并可进行再激活。 包括胎儿珠蛋白的表达（g-珠蛋白），60%-70% 珠蛋白合成基因表达产生 β地中海贫血特征珠蛋白合成比率，并且已经显示将贫血降低至轻度水平，这不需要常规输血 几类疗法诱导β地中海贫血患者中的g-珠蛋白的表达，升高了血红蛋白的总体水平，甚至让以前依靠输血的患者不再需要输血，这演示了此方法的概念验证。 不过，先前几代疗法未能进行广泛使用。 目前，最近发明的几种候选口服疗法更加有效和/或对病人更加友好，只需要少量口服剂量，它们具有不同的分子作用机制，可用于联合治疗方案。 将β+ 或β0珠蛋白变异和调节胎儿血红蛋白和临床严重性的数量性状基因（QTL）的病人单独分成几个类型，并给这些患者制定最佳治疗方案，这样开展的试验才会更有效和得到更多的信息。 通过这些尝试，可以提供合理的疗法，将胎儿珠蛋白基因诱导用于适合全世界地中海贫血患者使用的治疗方案之中。